Facebook as a virtual mosque: the online protest against Innocence of Muslims. Issue 1 (2nd January 2016) - Al-Rawi, Ahmed
Abstract: When the short anti-Islam film the Innocence of Muslims was first posted on YouTube in English, no tangible reactions were seen in the Arab world. However, when the same producer dubbed it into Arabic and posted it on YouTube, street protests started around some parts of the Arab world. The study reported here examines a popular Facebook page identified as The global campaign to counter the hurtful film against the Prophet Muhammed that was created to protest against the Innocence of Muslims film. This study investigated all 6949 Facebook updates and comments that were available on this page by 15 October 2012 and found that a clear majority of posts were Pro-Islamic focusing on prayers for Muhammed and supplications to defend him. This study advances our theoretical understanding of the connection between online and offline religion by providing empirical evidence in relation to this controversial incident.